The Evaluation of Torrefaction Efficiency for Lignocellulosic Materials Combined with Mixed Solid Wastes - Maja Ivanovski; Darko Goričanec; Danijela Urbancl (Energies, 2023)
The paper presents the results of research aimed at evaluating the possibility of using selected biomass wastes to produce solid biofuels. In this work, the thermochemical properties of two lignocellulosic biomasses, namely, miscantshus (Miscanthus × Giganteus) and hops (Humulus lupulus), and non-lignocellulosic biomass, namely, municipal solid waste, and their mixtures (micanthus + municipal solid waste and hops + municipal solid waste) were studied using the torrefaction process as the main method for investigation. The effects of various torrefaction temperatures (250, 300, and 350 °C) and times (30 and 60 min) were evaluated. Proximate and ultimate analyses were performed on the torrefied samples. The following can be stated: as the torrefaction temperature and time increased, mass and energy yields decreased while the higher heating values (HHVs) and fuel ratios (FRs) increased, together with carbon contents (C). In addition, energy on return investment (EROI) was studied; the maximum EROI of 28 was achieved for MSW biochar at 250 °C for 30 min. The results of studying greenhouse gas emissions (GHGs) showed a reduction of around 88% when using torrefied biochar as a substitute for coal. In sum, this study shows that torrefaction pre-treatment can improve the physicochemical properties of raw biomasses to a level comparable with coal, and could be helpful in better understanding the conversion of those biomasses into a valuable, solid biofuel.